No evidence for a BRD2 promoter hypermethylation in blood leukocytes of Europeans with juvenile myoclonic epilepsy. (4th February 2019) - Schulz, Herbert; Ruppert, Ann‐Kathrin; Zara, Federico; Madia, Francesca; Iacomino, Michele; S. Vari, Maria; Balagura, Ganna; Minetti, Carlo; Striano, Pasquale; Bianchi, Amedeo; Marini, Carla; Guerrini, Renzo; et al.
Summary: Juvenile myoclonic epilepsy (JME) is a common syndrome of genetic generalized epilepsies (GGEs). Linkage and association studies suggest that the gene encoding the bromodomain‐containing protein 2 ( BRD2 ) may increase risk of JME. The present methylation and association study followed up a recent report highlighting that the BRD2 promoter CpG island (CpG76) is differentially hypermethylated in lymphoblastoid cells from Caucasian patients with JME compared to patients with other GGE subtypes and unaffected relatives. In contrast, we found a uniform low average percentage of methylation (<4.5%) for 13 CpG76‐CpGs in whole blood cells from 782 unrelated European Caucasians, including 116 JME patients, 196 patients with genetic absence epilepsies, and 470 control subjects. We also failed to confirm an allelic association of the BRD2 promoter single nucleotide polymorphism (SNP) rs3918149 with JME (Armitage trend test, P = 0.98), and we did not detect a substantial impact of SNP rs3918149 on CpG76 methylation in either 116 JME patients (methylation quantitative trait loci [meQTL], P = 0.29) or 470 German control subjects (meQTL, P = 0.55). Our results do not support the previous observation that a high DNA methylation level of the BRD2 promoter CpG76 island is a prevalent epigenetic motif associated with JME in Caucasians.